Effectiveness of vehicle weight enforcement in a developing country using weigh-in-motion sorting system considering vehicle by-pass and enforcement capability - Karim, M.R.; Ibrahim, N.I.; Saifizul, A.A.; Yamanaka, H. (2013)
Vehicle overloading has been identified as one of the major contributors to road pavement damage in Malaysia. In this study, the weigh-in-motion (WIM) system has been used to function as a vehicle weight sorting tool to complement the exsiting static weigh bridge enforcement station. Data collected from the developed system is used to explore the effectiveness of using WIM system in terms of generating more accurate data for enforcement purposes and at the same time improving safety and reducing the number of vehicle weight violations on the roads. This study specifically focus on the effect of vehicle by-pass and static weigh station enforcement capability on the overall effectiveness of vehicle weight enforcement system in a developing country. Results from this study suggest that the WIM system will significantly enhance the effectiveness and efficiency of the current vehicle weight enforcement, thus generating substantial revenue that would greatly off-set the current road maintenance budget that comes from tax payers money. If there is substantial reduction in overloaded vehicles, the public will still gain through reduction in road maintenance budget, less accident risks involving heavy trucks, and lesser greenhouse gases (GHGs) emissions.